India and the patent wars : pharmaceuticals in the new intellectual property regime - Halliburton, Murphy, 1964- (Culture and politics of health care work., 2017)
India and the Patent Wars contributes to an international debate over the costs of medicine and restrictions on access under stringent patent laws showing how activists and drug companies in low-income countries seize agency and exert influence over ...